In situ Observations of Wave Transformation and Infragravity Bore Development Across Reef Flats of Varying Geomorphology - Cheriton, Olivia M.; Storlazzi, Curt D.; Rosenberger, Kurt J. (Frontiers in Marine Science, 2020)
The character and energetics of infragravity (‘IG’, 25 s < period < 250 s) and very-low frequency (‘VLF’, period > 250 s) waves over coral reef flats can enhance shoreline erosion or accretion, and also govern extreme shoreline events such as runup, overwash, and flooding on coral reef-lined coasts. Here we use in situ wave measurements collected along cross-reef transects at 7 sites on Pacific islands with varying reef geomorphologies to examine under what conditions IG waves occur and what factors enhance their irregularity. In general, a greater fraction of total wave energy was transferred to the IG band on reefs with steeper fore reef slopes and shallower reef flats. The IG wave amplitudes scaled with increasing water levels, but it was primarily at lower water levels when these waves became pitched onshore (negatively asymmetrical) and peaked (positively skewed). However, our results also highlight the importance of reef-flat width and slope as important morphological controls on IG waves, as the most asymmetric, bore-like, IG waves occurred on the wider reef flats, and the most skewed IG waves at the site with the steepest reef-flat. On the wider reef flats, IG wave-wave capture was observed during periods of large offshore wave forcing and enhanced VLF wave energy. Because similar IG wave motions over plane beaches enhance sea-swell (‘SS’, period < 25 s) bore-merging in the surf zone, we posit that VLF waves over reef flats may facilitate IG bore merging, and this may lead to larger, more pitched-onshore bores at the shoreline. In addition, greater IG wave heights appear to support the transmission of larger secondary short-period waves over the reef flat, independent of overall water levels. As irregular IG waves may be strong drivers of cross-reef sediment transport as well as runup, understanding the conditions and reef geomorphologies that lead to low-frequency, energetic bores on reef flats is critical to forecasting how coral reef-lined coasts will respond to sea-level rise and climate change.